2017
DOI: 10.13189/ujaf.2017.050202
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy among Women - Indian Scenario

Abstract: One of the biggest challenges of our country is women empowerment which can only be attained by making women educated, finance liberated and independent. Financial literacy can be understood as the ability to know how money works in a normal course of action. Specifically it refers to the set of skills and knowledge that allows an individual to make informed and effective decisions with all of their financial resources. In India, virtually women are the main spender of the family whereas the men are the princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 0 publications
2
35
0
1
Order By: Relevance
“…It can be observed that, even though their involvement and contributions have uplifted the evolution and the nature of community development, they have not been given proper acknowledgement for those contributions. The results of previous studies provide deeper insights into women's thinking about leadership and community development (Arora, 2016;Maheswari, 2016;Haque et al, 2018;Bonga et al, 2016;Singh et al, 2017;Lusardi et al, 2017;Roy et al, 2018). Therefore, based on the previous researchers' definitions and explanations, leadership in the community for present study means the extent to which poor rural women can influence the common decisions of community and degree of other community people willing to accept their views.…”
Section: Leadership In the Communitymentioning
confidence: 88%
See 4 more Smart Citations
“…It can be observed that, even though their involvement and contributions have uplifted the evolution and the nature of community development, they have not been given proper acknowledgement for those contributions. The results of previous studies provide deeper insights into women's thinking about leadership and community development (Arora, 2016;Maheswari, 2016;Haque et al, 2018;Bonga et al, 2016;Singh et al, 2017;Lusardi et al, 2017;Roy et al, 2018). Therefore, based on the previous researchers' definitions and explanations, leadership in the community for present study means the extent to which poor rural women can influence the common decisions of community and degree of other community people willing to accept their views.…”
Section: Leadership In the Communitymentioning
confidence: 88%
“…A study conducted by Hoque and Itohara (2009) reported that the time allocation is contributing to an extent in planning family activities and participating in family leisure time based on the decision making power of the rural women. The authors also stated that the time spending programme among family members contributes to develop the leadership of the rural women (Singh & Kumar, 2017;Deka, 2015;Karunathilake, 2016). This study was conceptualized by considering five important dimensions of WEE that identifies the basic five principles in which empowerment is achieved, in which control over the time allocation was identified as an important dimension (Swamy, 2014;Deka, 2015;Lusardi et al, 2017;Roy et al, 2018).…”
Section: Control Over the Time Allocationmentioning
confidence: 99%
See 3 more Smart Citations